2021
DOI: 10.1002/asia.202101157
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Study on Photophysical Properties of Mesoionic Chalcogenones

Abstract: N‐Heterocyclic carbene adducts with main group elements (NHC=E) have aroused great interest and have been widely investigated in coordination chemistry. Among them, N‐heterocyclic carbene adducts with chalcogens (NHC=Ch) have been known for a long time. Their investigations mostly focused on synthesis, coordination chemistry and electrochemistry. Their photophysical properties still remain unexplored. In this work, the photophysical properties of mesoionic carbene adducts with sulfur and selenium have been inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 75 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…Recently our group investigated the photophysical properties of MICderived chalcogenones (MIC=Ch). [20] We found that MIC=Ch exhibited very low QYs in DCM solution, which is between 0.13% and 4.0%. The totally difference in QYs between 4-6 and MIC=Ch can be ascribed to the various transition mode from S0 Scheme 2.…”
Section: Resultsmentioning
confidence: 73%
See 4 more Smart Citations
“…Recently our group investigated the photophysical properties of MICderived chalcogenones (MIC=Ch). [20] We found that MIC=Ch exhibited very low QYs in DCM solution, which is between 0.13% and 4.0%. The totally difference in QYs between 4-6 and MIC=Ch can be ascribed to the various transition mode from S0 Scheme 2.…”
Section: Resultsmentioning
confidence: 73%
“…The length of C2−N1 is 1.296 Å, which is identical with that of its analogs, imidazolin‐2‐imine (1.296 Å), [12] and it is in the range of length of partial double bonds to length of single bond (1.279 Å to 1.465 Å), [13] according with the calculated Wiberg bond order (1.78). The bond length of C1−C2 is 1.430 Å, which is longer than other MICs and their derivatives, such as triazolium (1.357 Å to 1.387 Å), [14–17] N ‐heterocyclic olefins (mNHOs) (1.417 Å to 1.418 Å) [18–19] and mesoionic chalcogenones (MIC=Ch) (1.398 Å to 1.412 Å) [20] . This is due to the strong electronegativity of exocyclic nitrogen atom as well as the π lone pair electrons on of the exocyclic nitrogen atom, which results in a more delocalized π system.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations